2011
DOI: 10.1007/bf03325756
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear control method for the electromagnetic suspension system of the maglev train

Abstract: Abstract:To deal with the inherent nonlinearity and open-loop instability of the electromagnetic suspension (EMS) system, a new nonlinear control method is proposed. The simulation results show that, for a PID controller, the overshoot of the system response to an airgap step disturbance is about 3 mm, and the transient time is 6 s; however, for the proposed nonlinear controller, there is no overshoot and transient time within 2 s. The proposed method has a faster response and stronger robustness. With a desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Some parameters of the electromagnetic suspension system are presented in Table 13.1 (other sets of parameters can be found in [103,183,231]), and the allowable bounds of θ(k) are listed in Table 13.2. With the parameters given in Tables 13.1 Constructing a non-PDC fuzzy controller by (13.27), we can get the system states of the closed-loop system.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some parameters of the electromagnetic suspension system are presented in Table 13.1 (other sets of parameters can be found in [103,183,231]), and the allowable bounds of θ(k) are listed in Table 13.2. With the parameters given in Tables 13.1 Constructing a non-PDC fuzzy controller by (13.27), we can get the system states of the closed-loop system.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Systems, such as that in high-speed maglev passenger trains [231,105], levitation of wind tunnel models, levitation of molten metal in induction furnaces, vibration isolation and frictionless bearings, are mostly based on electromagnetic suspension systems. Therefore, in this view, electromagnetic suspension systems can be regarded as repulsive system or attractive system which is based on the source of electromagnetic levitation forces.…”
Section: Introductionmentioning
confidence: 99%
“…State feedback control can be directly adopted in nonlinear systems. Xu and Zhou et al [82] adopted the state feedback control method to replace the nonlinear part in the nonlinear maglev system. The electromagnetic force was decomposed into four parts for controller design.…”
Section: State Feedback Control Algorithmsmentioning
confidence: 99%
“…The malfunction of suspension controller means that the suspension controller fails to suspend the maglev train within a certain range. Experiments have indicated that the malfunction of the suspension control system easily occurs when the linearized model is subjected to interference [11]. In addition, malfunction of the suspension control system can be caused by the failure of its components such as the abnormal of suspension sensors (including gap, current, and acceleration sensors), the short circuit failure, the electromagnet with a less effective number turn or higher temperature, the earth leakage failure of electromagnet, and the failure of power supply [12][13][14].…”
Section: Introductionmentioning
confidence: 99%